Incidence of team level on performance of skills in volleyball - Palao, J. M.; Santos, J. A.; Urena, A. (World Congress of Performance Analysis of Sport 6, 22-25 June 2004, St. Mary's University College - Book of Abstracts, 2004)
The present paper studies the effect of a team's level on the performance of skills (serve, reception, spike, block and dig) in high level volleyball. Thirtythree male matches and 23 female matches of the Olympic Games of Sydney 2000 were recorded and analyzed. The performance of skills was evaluated in relation to the success and options that these skills give to one's team and to the opposite team. The team's level was established in relation to the final classification of the team in the competition (level 1: 1st - 4th ; level 2: 5th - 8th ; & level 3: 9th - 12th ). Ten observers participated in the study. Inter- and intra-observer reliability coefficients of the studied variables were calculated (r > 0.92) after training and during the analysis. In males, the results show a significant difference between teams' levels for the skills of spiking and blocking. The block is the skill that differentiates the teams of level 1 with the teams of level 2. A reduction of error in relation to the level of the team is observed. In females, we found a significant difference in the performance of the spike in the teams of level 1. An increase in success of reception, spike, block and dig in relation to the level of the team is observed.